Ueber Reinheit der Tonkunst - Thibaut, Anton Friedrich Justus 1772-1840 (Heidelberg Mohr, 1825)
Thibaut, a man of strong personality, was much more than a jurist: he has a place in the history of music. Palestrina and the early composers of church music were his delight; and in 1824 he published, anonymously, Über die Reinheit der Tonkunst (Purity of Music), in which he eulogized the music of Palestrina and Handel against post-Mozartian church music, "which he considered not only impure and immoral, but also unnatural, submitting to the secular, arrogant and idle trends of modern music, and deprived of the simple, childlike melodies which naturally spring from the people (or so he imagined)." (Björn Schmelzer, 'The Monstrosity of Early Music: Revivalism and the Excess of Musical Survivals', Bäsler Jahrbuch für historische Musikpraxis 2024, 367-404: 374). He was an ardent collector of old compositions, and often sent young men to Italy, at his own expense, to discover interesting musical manuscripts.
Contains a delicate portrait of Palestrina
Ex Libris H. O. (Plate)
Keywords: Palestrina, Giovanni Pierluigi da -- c. 1525-1594; Handel, George Frideric -- 1685-1759; 19th Century (1801-1900); Renaissance (1400-1600); Music history; Music theory; Music criticism; Early music; Accuracy; Germany; a capella; ad lib bezetting; afwisseling; Anerio; Bach, J.S._na dood; bibliotheek; boekprijs; bc; Beethoven; Benevoli, O; Bertoni; Caldara, A; Carissimi; Cherubini; Naumann; compositieloon; contrabas; orgel in eredienst; oud-nieuw; oude muziek vroeger; Palestrina; dirigent; Pergolesi; Durante; emoties; publiek; Forkel, N; Glück; Graun; trompet; harp; Valotti; Hasse, J.A.; Haydn, J; Haydn, M; Homilius; voc.-instr. muziek; volume; jongenssopraan; Josquin; kerkmuziek; koraal en tussenspelen; Lasso, O. di; Leo, L; Scarlatti, A; Lotti, A; Senfl, H; slagwerk; Marcello, B; morales